Compartmental and temporal dynamics of chronic inflammation and airway remodelling in a chronic asthma mouse model. - Mohammed Alrifai (Public Library of Science (PLoS), 2014)
Background Allergic asthma is associated with chronic airway inflammation and progressive airway remodelling. However, the dynamics of the development of these features and their spontaneous and pharmacological reversibility are still poorly understood. We have therefore investigated the dynamics of airway remodelling and repair in an experimental asthma model and studied how pharmacological intervention affects these processes. Methods Using BALB/c mice, the kinetics of chronic asthma progression and resolution were characterised in absence and presence of inhaled corticosteroid (ICS) treatment. Airway inflammation and remodelling was assessed by the analysis of bronchoalveolar and peribronichal inflammatory cell infiltrate, goblet cell hyperplasia, collagen deposition and smooth muscle thickening. Results Chronic allergen exposure resulted in early (goblet cell hyperplasia) and late remodelling (collagen deposition and smooth muscle thickening). After four weeks of allergen cessation eosinophilic inflammation, goblet cell hyperplasia and collagen deposition were resolved, full resolution of lymphocyte inflammation and smooth muscle thickening was only observed after eight weeks. ICS therapy when started before the full establishment of chronic asthma reduced the development of lung inflammation, decreased goblet cell hyperplasia and collagen deposition, but did not affect smooth muscle thickening. These effects of ICS on airway remodelling were maintained for a further four weeks even when therapy was discontinued. Conclusions Utilising a chronic model of experimental asthma we have shown that repeated allergen exposure induces reversible airway remodelling and inflammation in mice. Therapeutic intervention with ICS was partially effective in inhibiting the transition from acute to chronic asthma by reducing airway inflammation and remodelling but was ineffective in preventing smooth muscle hypertrophy.